The Dictatorship of nationalism Great Serbian expansionism, ethnic perversion and "The will of people": Text is published in periodical "Survey" 3-4, 2007 - Lavić, Senadin (Pregled: časopis za društvena pitanja / Periodical for social issues, 2008)
Can the crime and its practical institutional and political results in the territory of Bosnia and Herzegovina be justified, without immorally and inhumanly humiliating the victims and the sense of human existence? That is one of the questions motivating the text. We are driven into a corner, or to an almost hopeless situation when facing this kind of question, in which we learn about the dark side of human existence. What does, in fact, a victim need to do in order to prevent the repetition of crimes against it and why does the victim become suspicious of the international institutions, human rights declarations and stories about the achievements of our time? All that has a global and local value of representation. Furthermore, does the acceptance of the results of crime (silent consent to crimes) mean that one can, in the future, expect the same actions of physical extinction of a people, which have proven to be genocidal? Experience of the victim is that the international community never reacts timely – the international peacekeepers and the Owl of Minerva come “when all passes away “or at the “end of the day”, or when everything is covered with mass graves. Democracy and enlightenment can even further disown the unbearable dictatorship of nationalism and ethnic monarchies in some parts of Bosnia and Herzegovina.